การพัฒนาทักษะการชั่ง ตวงวัตถุดิบในรายวิชาขนมไทย ผ่านการเรียนรู้แบบร่วมมือกับการใช้แบบฝึกปฏิบัติด้านอาหาร สำหรับนักเรียนประกาศนียบัตรวิชาชีพ - สิงหบุญพงศ์ ทัศนีย์; สิงหบุญพงศ์ ธิดารัตน์; วิจิตรวรรณา สมถวิล (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to 1) developing skills in weighing and measuring ingredients in the Thai Desserts course through cooperative learning and using food practice kits and 2) study student satisfaction with the learning process. The research was conducted with a population of 24 Second-year vocational certificate students at Pongsawat Technological College, Semester 2, Year 2025. The research instruments were lesson plans, tests, and a 5-level rating questionnaire. Data were analyzed using basic statistics, mean, and standard deviation. The research findings revealed that 1. students who received cooperative learning with the use of food practical kits showed higher weighing and measuring ingredients than pre-test. 2. Overall student satisfaction was at the highest level.